Abnormal Expression of miR-21 in Kidney Tissue of Dogs With X-Linked Hereditary Nephropathy: A Canine Model of Chronic Kidney Disease. Issue 1 (January 2019) - Clark, Sabrina D.; Song, Wenping; Cianciolo, Rachel; Lees, George; Nabity, Mary; Liu, Shiguang
MicroRNAs (miRNAs) are a group of small noncoding RNAs that act as regulators of posttranslational gene/protein expression and are known to play a key role in physiological and pathological processes. The objective of our study was to compare expression of miR-21 in renal tissue from dogs affected with chronic kidney disease (CKD) caused by X-linked hereditary nephropathy (XLHN), a disease equivalent to human Alport syndrome, to that from unaffected dogs. Additionally, we sought to characterize changes in relative mRNA expression of various genes associated with miR-21 function. miRNA was isolated from kidney tissue collected from both affected dogs and unaffected, age-matched littermates at defined milestones of disease progression, including end-stage renal disease (ESRD). Additionally, autopsy samples from affected dogs at ESRD and corresponding unaffected dogs were evaluated. Samples were scored based on histological changes, and relative expression of miR-21 and kidney disease-related genes was determined using quantitative real-time polymerase chain reaction. In affected dogs, significant upregulation of kidney miR-21 was first detected at the milestone corresponding with increased serum creatinine. Furthermore, miR-21 expression correlated significantly with urine protein: urine creatinine ratio, serum creatinine concentration, glomerular filtration rate, and histologic lesions (glomerular damage, tubular damage, chronic inflammation, and fibrosis). At end-stage disease, COL1A1, TGFB1 and its receptor, TGFB2, and Serpine1 were upregulated, while PPARA, PPARGC1A, ACADM, SOD1, and EGF were downregulated. In conclusion, miR-21 is abnormally upregulated in the kidneys of dogs with CKD caused by XLHN, which may play an important pathologic role in the progression of disease by dysregulating multiple pathways.